Limited sensitivity and specificity of the ACR/EULAR-2019 classification criteria for SLE in JSLE?—observations from the UK JSLE Cohort Study. (4th March 2021) - Smith, Eve M D; Rasul, Sajida; Ciurtin, Coziana; Al-Abadi, Eslam; Armon, Kate; Bailey, Kathryn; Brennan, Mary; Gardner-Medwin, Janet; Haslam, Kirsty; Hawley, Daniel P; Lane, Steven; Leahy, Alice; et al.
Abstract: Objectives: This study aimed to test the performance of the new ACR and EULAR criteria, that include ANA positivity as entry criterion, in JSLE. Methods: Performance of the ACR/EULAR-2019 criteria were compared with Systemic Lupus International Collaborating Clinics (SLICC-2012), using data from children and young people (CYP) in the UK JSLE Cohort Study ( n = 482), with the ACR-1997 criteria used as reference standard. An unselected cohort of CYP positive for ANA ( n = 129) was used to calculate positive/negative predictive values of the criteria. Results: At both first and last visits, the number of patients fulfilling the different classification criteria varied significantly ( P < 0.001). The sensitivity of the SLICC-2012 criteria was higher when compared with that of the ACR/EULAR-2019 criteria at first and last visits (98% vs 94% for first visit, and 98% vs 96% for last visit; P < 0.001), when all available CYP were considered. The ACR/EULAR-2019 criteria were more specific when compared with the SLICC-2012 criteria (77% vs 67% for first visit, and 81% vs 71% for last visit; P < 0.001). Significant differences between the classification criteria were mainly caused by the variation in ANA positivity across ages. In the unselected cohort of ANA-positive CYP, the ACR/EULAR-2019 criteria produced the highest false-positive classification (6/129, 5%). Conclusion: In CYP, the ACR/EULAR-2019 criteria are not superior to those of the SLICC-2012 or ACR-1997 criteria. If classification criteria are designed to include CYP and adult populations, paediatric rheumatologists should be included in the consensus and evaluation process, as seemingly minor changes can significantly affect outcomes.